Analysis of Fraudulent Cases in Procurement of Goods and Services at State-Owned Enterprise Pertamina: Oil Adulteration and Its Impact on the National Economy - Khairani, Dinda; Santika, Icha; Nasution, Muhammad Mandala; Yoandika, Ridho; Rizkina, Miftha (EDUCTUM: Journal Research, 2025)
The case of adulterated fuel (BBM) involving the Pertamina brand is a serious issue that impacts economic stability, consumer safety, and the credibility of state-owned enterprises. This study aims to analyze the perpetrators' modus operandi, the economic and social impacts of the adulterated practice, and the efforts made by the authorities and Pertamina in handling the case. The method used in this study is a qualitative approach with literature studies and mass media analysis as the main data sources. The results of the analysis indicate that the adulterated practice is generally carried out by mixing official fuel with low-quality materials to obtain greater profits, which has a negative impact on vehicle performance and the environment. In addition, weak supervision of fuel distribution is a major loophole for violations. This study recommends strengthening the supervisory system, increasing distribution transparency, and public education about the dangers of adulterated fuel. Integrated handling between Pertamina, law enforcement officials, and the community is needed to prevent similar cases in the future.